A Step Down Transformerless Single Switch Integerated Buck and Buck-Boost Converter - P. Maithili; C. Tharani; J. Nivedha; D. Soundarrajan (Institute of Advanced Engineering and Science, 2016)
This paper presents about the designing of the controller for integrated Buck Buck-Boost converter for maintaining the constant DC output voltage. This constant output voltage can be used for low voltage application. The absence of transformer includes the advantages of losses is less, efficient power factor and high efficiency. It provides the simple control structure with the positive constant output voltage .It operates on the closed loop with the designing of the PI controller for a MOSFET switch to provide the gate pulse. Whatever may be the input voltage it will produce the constant output voltage. The converter is successfully done by using MAT Lab/Simulink and verified the error reducing to negligible values.